Formulation Development for the Production of Poly(lactic acid)-based Films for Use as Biodegradable Packaging Materials for Dried Longan - Sutinee Girdthep (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Biodegradable polymer nanocomposites have been developed in this study as materials for use in the packaging of moisture-sensitive products. Poly(lactic acid) (PLA) was the main component of the nanocomposites with poly(butylene adipate-co-terephthalate) (PBAT) as flexibility enhancer. Tetrabutyl titanate (TBT) was also added as a compatibilizer to enhance the interfacial affinity between PLA and PBAT by inducing the formation of some PLA/PBAT via transesterification during the melt blending process, thereby improving the mechanical properties of the blends. Silver-loaded kaolinite (AgKT) synthesized via chemical reduction was also incorporated into the compatibilized blends for further property improvement. Herein, we report a novel biodegradable quaternary nanocomposite system with intercalated-exfoliated clay dispersion that was uniquely achieved by increasing the interlamellar space between kaolinite layers through silver nanoparticle insertion. The resultant compressed sheets of nanocomposites containing as little as 4 phr modified clay reduced the elongation at break from 213.0 ± 5.85 % to 53.8 ± 1.81 %, enhanced thermal stability (initial decomposition temperature increased from 378 C to 399 C) and exhibited a water vapor permeability (WVP) reduction of 41.85 %.